The determinants of job satisfaction: organizational commitment and organizational citizenship behavior - Jouse Bastian; Ginanjar Syamsuar (Jurnal Riset Manajemen dan Bisnis, 2025)
This study aims to analyze the determinants of job satisfaction, specifically the influence of organizational commitment and organizational citizenship behavior (OCB), within micro enterprises in Duren Sawit, East Jakarta. A quantitative approach was employed, utilizing primary data collected via questionnaires from micro-enterprise employees. As the exact population size was unknown, the Lemeshow formula was applied for sampling. The data were analyzed using SmartPLS 3.0, which employs a variance-based Structural Equation Modeling (SEM) approach, also known as Partial Least Squares (PLS), to test the hypothesized relationships between variables. The results confirm that both organizational commitment and organizational citizenship behavior have a significant positive influence on job satisfaction. These findings highlight the crucial role of fostering employee dedication and promoting voluntary, constructive behaviors in enhancing satisfaction within the micro-enterprise context.